KEEPING THE NATION'S ASSETS THROUGH THE LEGAL PROTECTION OF COPYRIGHT WORKS OF CULTURE - Zulkifli Makkawaru (Indonesia Prime, 2016)
Indonesia positioned copyright art and culture based on its strength as a nation or community rights over an Alliance grouping of the society which can give the effect of distortions in its protection. Which institution can be megurus and oversee the interests between countriesCultivate ideas/ideas in the fields of art, literature and science in the context of intellectual property rights (HKI) categorized into areas of HKI named Copyright (Copyright). The scope of the rights provided for the protection of copyright in the context of this very broad following elements known in several countries. There is a different understanding about the copyright status of culture from both the substance of the right nor of the appreciation of the case which threatens foreign claims copyright over the culture of Indonesia